2013
DOI: 10.1155/2013/932040
|View full text |Cite
|
Sign up to set email alerts
|

SpecificDioscoreaPhytoextracts Enhance Potency of TCL-Loaded DC-Based Cancer Vaccines

Abstract: Dioscorea tuber phytoextracts can confer immunomodulatory activities ex vivo and improve regeneration of bone marrow cells in vivo. In present study, we evaluated specific Dioscorea phytoextracts for use ex vivo as a bone-marrow-derived dendritic cell- (DC-) based vaccine adjuvant for cancer immunotherapy. Fractionated Dioscorea extracts (DsII) were assayed for their effect on maturation and functions of DC ex vivo and antimelanoma activity of DC-based vaccine in vivo. The phytoextract from 50–75% ethanol-prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 39 publications
1
34
1
1
Order By: Relevance
“…The suboptimal maturation of DCs, which expressed low levels of co-stimulatory and MHC molecules and Th1-polarizing cytokine IL-12, is the one of the reason that caused the limited success of DCbased vaccine in clinical trials [39][40][41]. It has reported that extracts of herbal medicines can enhance anti-tumor immune responses through promoting the maturation and function of DCs [14][15][16][17]. Here, we found that PFWE not only enhanced the maturation of DCs and but also increased the production of IL-12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suboptimal maturation of DCs, which expressed low levels of co-stimulatory and MHC molecules and Th1-polarizing cytokine IL-12, is the one of the reason that caused the limited success of DCbased vaccine in clinical trials [39][40][41]. It has reported that extracts of herbal medicines can enhance anti-tumor immune responses through promoting the maturation and function of DCs [14][15][16][17]. Here, we found that PFWE not only enhanced the maturation of DCs and but also increased the production of IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence including ours indicates that herbal medicine and its components can regulate the maturation and function of DCs to promote the Th1 and CTL responses [12][13][14][15]. Elluru et al [16] showed that aqueous extracts from Viscum album stimulate the maturation and activation of human DCs, which may facilitate anti-tumoral immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…DCs generated in this manner were mainly immature DCs (85% of cells are CD11c + ) and displayed the typical morphologic features of DCs. [66]…”
Section: Methodsmentioning
confidence: 99%
“…Activation of bone marrow-derived DCs (BMDCs) was performed as previously described [66]. Briefly, BMDCs were incubated for 2 h with various test tumor cell lysate (TCL) samples containing 200 μg protein/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation